Iridium-catalyzed [4 + 2] annulation of 1-arylindazolones with α-diazo carbonyl compounds: access to indazolone-fused cinnolines - Markad, D.; Mandal, S.K. (Royal Society of Chemistry, 2018)
An efficient one-pot Ir-catalyzed method was developed for the synthesis of indazolone-fused cinnolines by [4 + 2] annulation of 1-arylindazolones with α-diazo carbonyl compounds via sequential C–H activation/carbene insertion/cyclization in a tandem manner. This method has excellent tolerance towards electron-withdrawing and electron-donating functional groups on 1-arylindazolone. This method was also found to be applicable to cyclic α-diazo carbonyl compounds.
Only IISERM authors are available in the record.
Keywords: Carbonyl compounds; Electron-donating; Activation analysis; Iridium